Optimization of cutting parameters using Taguchi method during the face milling of AISI 1040 with coated and uncoated inserts - Gürcan SAMTAŞ (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
AISI 1040 carbon steel is used in many different sectors such as mold sets, automobile components, transmission shafts, rails and gears. The use of this material in different sectors, its behaviors in the various machining operations have become important. In this study, face milling process was applied to AISI 1040 carbon steel material by using coated and uncoated cutting inserts. Experiments were performed on the basis of Taguchi’s L18 orthogonal array (OA) at different levels of the cutting inserts (Uncoated carbide, CVD / TiN-TiCN-Al2O3 coated carbide, PVD/TiALN coated carbide), the cutting speeds (160, 180, 220 m/min) and the feed rate (0.1, 0.15, 0.3 mm/tooth) and relating to a good surface quality using 0.3 and 0.6 mm cutting depths in whole experiments. The obtained values at the end of the experiments were evaluated through the signal to noise (S/N) ratios and Analysis of Variance (ANOVA). The end of the confirmation experiments, the machining accuracy of 2.90 µm could be significantly improved to 1.42 µm with an enhanced performance of 51.03%.